Contribution of Woman Forest Farmers on Family Income at Private Forest in Air Kubang Village Air Naningan District Tanggamus Regency - Lubis, Rini Sari; Kaskoyo, Hari; Febryano, Indra Gumay; Bakri, Samsul (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
The contribution of women forest farmers in managing their forest land can help improve the family's economy. The purpose of this study was to analyze the total income of woman, total family income and identify the contribution of woman roles on family income. Data was collected through interviews using a structured questionnaire to 55 respondents that selected by simple random sampling. Qualitative data analysis used to identify economics forms of woman forests farmers, whereas quantitative data analysis used to analyze total income of women forests farmers, total family income, and contribution of women forests farmers roles. The results showed that the average income of woman forest farmers was Rp 475.000/month, family income was Rp 1.428.000/month, and 42 women or around 76% had relatively small contributions because 50% from total family income and 24% or 13 people were able give their contribution that is big enough because >50% from total family income. Key words: contribution, private forest, woman forest farmer income